Inovasi dalam Pelayanan Publik: Penggunaan Teknologi untuk Meningkatkan Efektivitas Layanan Pemerintah - Muhammad Atha’ Iqbal; H. Moh. Juhad (Jurnal Media Administrasi, 2026)
This study examines the application of innovation in public services based on digital technology as a strategic approach to improve the effectiveness, efficiency, transparency, and overall quality of government services. The digitization of service delivery through e-government initiatives, smart governance frameworks, and various applications such as SEPP, E-Lapor, JAKI, and OpenSID has been proven to accelerate administrative processes, simplify complex bureaucratic procedures, and significantly expand public access to services. In addition, these digital platforms contribute to more inclusive and user-oriented public service systems. The purpose of this study is to analyze the effectiveness of technology in improving service delivery and to identify strategic steps that can be taken to address the challenges associated with service innovation in the public sector. Qualitative research methods were applied, utilizing data collection techniques through an extensive literature review of relevant academic and policy sources. The findings illustrate that technology-based innovation not only supports improved service performance but also strengthens accountability, responsiveness, and public participation in governance processes.